(untitled) (Libellarium: journal for research in the field of information and related sciences, 2015)
This paper intends to reposition “publishing studies” in the long process that goes from the beginning of book history to the current research on cultural industries. It raises questions about interdisciplinarity and the possibility of considering publishing independently of other sectors of the media and cultural offerings. Publishing is now included in a large range of industries and, at the same time, analyses tend to become more and more segmented according to production sectors and scientific fields. In addition to the problems created, from the professional point of view, by this double movement, this one requires a questioning of the concept of “publishing studies”.